Pelatihan Pengolahan Minyak Jelantah Sebagai Dasar Pembuatan Lilin Warna-Warni Di Kelompok Ibu PKK Karang Menjangan - Devianti, Vika Ayu; Sa'diyah, Lailatus; Silvi Ayu Wulansari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The community service carried out by the Surabaya Pharmacy Academy team aims to increase public awareness about the dangers of used cooking oil regarding the potential diseases that can occur if consumed continuously. The waste cooking oil produced is processed into colorful candle products. The colorful candles produced can be used as lighting at home or can also be used as room decoration because of their attractive colors and shapes. Based on the results of this community service, the community was very enthusiastic and gave a positive response to this training. The community has new insight into processing used cooking oil waste into colorful candles. People can practice making colorful candles again at home. This product can also be a creative and innovative business idea.